Distributive Trades Journal
Since (1939):no.5 subtitled: Official Organ of the National Amalgamated Union of Shop Assistants, Warehousemen and Clerks. - Continues: Shop Assistant, A journal for all... (ZDK 6785). - Continued by: The New Dawn. Official Organ of the National of Distributive and Allied Workers (ZO 6040).